Aspectos relacionados con la motivación, el sentido de vida y libertad en una persona alcohólica - Ovalle Escarraga, Daniel Felipe (Universidad Antonio Nariño, 2021)
The present investigation looked for the aspects related to motivation, life sense and freedom in an alcoholic person, it got looked for a person who is a participant active in alcoholic anonymous group , this person is 41 years old, member of AA for 12 years, making two interviews , from each of them, there were 3 categories and 1 emergent category, these are: family factors, sporting factors, related with persons of the institution who produce motivation for recovery process, experiences related with freedom feelings, inside and outside of recovery process, experiences related with family and another people of environment who produce life sense and social criticism around the recovery process (emergent) this categories emerge according to predominant concepts that this person mentioned frequently